Manajemen Komite Sekolah dalam Mencapai Mutu Pendidikan Berkualitas Pada UPTD SPF SD Negeri Pandan Sari Gunung Meriah - Sulaiman Ibrahim (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The school committee is an independent body that accommodates community participation in improving the quality, equity, and efficiency of education management in educational units. This study aims to: (1) describe the management of the School Committee in achieving quality education at UPTD SPF SD Negeri Pandan Sari Gunung Meriah; and (2) analyze the implementation of the School Committee's functions so that they can run effectively in achieving quality education at UPTD SPF SD Negeri Pandan Sari Gunung Meriah. This study uses a qualitative approach with a field research type. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, and verification/conclusion drawing. The results show that: (1) The management of the School Committee in achieving quality education covers three stages: (a) Program Planning, including planning for the procurement of qualified educators and education staff, planning for the provision of facilities and infrastructure, and planning for teacher competency enhancement training; (b) Program Implementation through meetings with the school and parents, forming committees, fundraising, and physical and non-physical program implementation; and (c) Program Evaluation through direct classroom observation, quality control of school policies, and monitoring of the budget and facilities; (2) The implementation of the School Committee's functions runs effectively through efforts to encourage community participation, provide recommendations to the principal, raise funds, improve facilities, add student learning hours, and organize talent-based extracurricular activities.